Medo e violência na cidade: imagens, discursos e sociabilidade nas praças de João Pessoa - PB - Campos, Ricardo Bruno Cunha (2014)
The present work analyses and discusses the sociability in the culture of contemporary cities focusing on the theme of fear and violence in the daily life of squares in the city of João Pessoa-PB. We analyse the relations between places in town and make correlations of history and setting of neighborhoods with the process of urban growth, including recent interventions of public authorities in their public spaces. We observed in this dynamics social attitudes and actions that range from a desired peaceful coexistence to social exclusion. Thus, we discuss, based upon the imaginary vision, that the squares exist as a locus of equality, citizenship and political, and, also, as a space for everyone, despite the existence of symbolic forces working towards segregation and privatization, ruled in fear and violence. We aimed to investigate the different symbolic logics from the issue of fear and violence that allows the exclusion and the inclusion of groups and individuals in the quotidian use of public spaces of contemporary cities. We believe that the social action is demarcated by violence ant its corollary, the social fear, and operates based on the logic of a relational game always confrontational but experienced in different forms according to the social segment or group under study. We used a qualitative and quantitative methodology relating data and statistical analysis with categories created for the understanding of subjective factors. Our analyses combined ethnographic elements, periodics research and images of the city and its spaces, with the contribution of a survey that allowed comparisions of five squares of neighborhood based on the daily life under investigation. Our proposal was to deepen the investigations related to the public space of contemporary cities, expanding the look on João Pessoa and its cultural dynamics with an analysis of discourses, images, the collective imaginary and the social appropriation of the spaces based on fear and violence. The research accomplished in different areas and the analysis of images and speeches published in newspapers reports, books, advertising etc. allowed the approach of differentiated patterns of sociability in the same urban process. The neighborhoods in study are indeed spatially and economically distanced and the process of creation and construction of squares occurred in very different ways in the respective location. We defend the thesis that neighborhood community squares provide reinvigorated spaces and public spheres in the urban process and in the dynamics of sociability in the cities. These squares are also social spaces par excellence for the perception of the logic of individualism and segregation so marked by fear and violence in contemporary cities